MicroRNA signatures: novel biomarker for colorectal cancer? - Luo, Xiaoya; Burwinkel, Barbara; Tao, Sha; Brenner, Hermann (Cancer epidemiology, biomarkers & prevention, 2011)
Aberrant microRNA (miRNA) expression might be of potential use as diagnostic and prognostic biomarker for cancers. We reviewed studies published until March 2011 which assessed expression of miRNAs in colorectal cancer (CRC)/adenoma tissue and normal colorectal mucosa and in plasma of CRC/adenoma patients and healthy controls. Overall, 20 studies that investigated miRNA expression in tissue and 3 studies that investigated miRNA levels in plasma were included. A total of 160 miRNAs were found to be dysregulated in CRC. MiR-20a and miR-31 were found to be significantly upregulated in more than one study, and miR-143 and miR-145 were found to be significantly downregulated in CRC tissue in six or more studies. MiR-92a was significantly upregulated in CRC patients in two of the plasma-based studies and in CRC tissue in one of the tissue-based studies. Our results provide timely and relevant information for miRNAs as potential diagnostic biomarkers for CRC. The expression of miRNAs in plasma may be indicative of presence of CRC. Larger diagnostic studies are needed to evaluate potential use of miRNA expression in early detection and diagnosis of CRC. Cancer Epidemiol Biomarkers Prev; 20(7); 1272-86. ©2011 AACR.